Criminalizing the Guardians: Eco-Justice and Indigenous Struggles in Indonesia and Nigeria - Adiyatma, Septhian Eka; Silviana, Ana; Dorcas Adesola Thanni (Universitas Negeri Semarang, 2025)
This study examines the criminalization of Indigenous communities in Indonesia and Nigeria within the broader framework of ecological justice and natural resource governance. Using a normative legal research method combined with a comparative approach, the research explores how state–corporate alliances and positivist legal paradigms perpetuate structural injustice against Indigenous environmental defenders. Findings reveal that the law, instead of serving as an instrument of protection, often legitimizes ecological exploitation and marginalization through selective enforcement and the absence of robust safeguards for Indigenous land rights. The study introduces the eco-justice and ecocide frameworks as normative foundations for transforming criminal law toward a more equitable and ecocentric model. Eco-justice demands the integration of distributive, procedural, and recognition justice in environmental decision-making, while the concept of ecocide expands criminal liability to cover large-scale and systemic environmental destruction. Comparative insights from Sweden further illustrate that genuine ecological justice requires multi-layered protection combining legal recognition, participatory consultation, and judicial precedents that affirm Indigenous sovereignty over natural resources. This research argues that recognizing Indigenous communities as legitimate legal subjects and incorporating ecocide into national criminal law constitute essential steps toward restoring balance between human rights and the rights of nature.